The Role of NGO in Overcoming the Environmental and Food Crisis in Indonesia During the COVID-19 Pandemic - Tresea .; Sulistiarani .; Kinanti Tamara; Azhar . (Frequency of International Relations (FETRIAN), 2021)
Covid-19 is a new threat that has had a very influential in recent times. The world health organization, namely the WTO, has conveyed the urgency regarding the global pandemic which is a threat to world safety and health. The high number of Covid-19 cases has an impact on human security problems including health, hunger, death, large-scale economic decline, and increasing poverty rates. This human security problem occurs in all countries around the world, including in Indonesia. Food scarcity has led to an increase in food prices, plus limited work activities have made this pandemic an extraordinary issue. Walhi, which is a local non-governmental organization, is present in the midst of the deteriorating quality of life of the Indonesian people to carry out its role. Walhi itself is an NGO which often makes notes on ecological disasters that often occur in Indonesia, including food crises and other crises caused by environmental problems. Walhi is also working with FAO in dealing with impacts humanitarian pandemic Covid-19. This group of organizations is trying to assist in overcoming this crisis.